Working Conditions, Job Strain, and Traffic Safety among Three Groups of Public Transport Drivers - Sergio A. Useche; Viviola Gómez; Boris Cendales; Francisco Alonso (Elsevier, 2018)
Background: Working conditions and psychosocial work factors have acquired an important role explaining the well-being and performance of professional drivers, including those working in the field of public transport. This study aimed to examine the association between job strain and the operational performance of public transport drivers and to compare the expositions with psychosocial risk at work of three different types of transport workers: taxi drivers, city bus drivers, and interurban bus drivers. Method: A sample of 780 professional drivers was drawn from three transport companies in Bogota (Colombia). The participants answered the Job Content Questionnaire and a set of sociodemographic and driving performance questions, including age, professional driving experience, work schedules, and accidents and penalties suffered in the last 2 years. Results: Analyses showed significant associations between measures of socio-labor variables and key performance indicators such road traffic accidents and penalties. Furthermore, multiple linear regression analysis contributed to explain significantly suffered accidents from key variables of the Job Demand-Control model, essentially from job strain. In addition, throughout post-hoc analyses, significant differences were found in terms of perceived social support, job strain, and job insecurity. Conclusion: Work stress is an issue that compromises the safety of professional drivers. This research provides evidence supporting a significant effect of job strain on the professional driver's performance. Moreover, the statistically significant differences between taxi drivers, city bus drivers, and interurban bus drivers in their expositions to work-related stress suggest the need for tailored occupational safety interventions on each occupational group. Keywords: Job strain, Professional drivers, Psychosocial factors at work, Road traffic accidents, Working conditions